2020
DOI: 10.1534/g3.120.401147
|View full text |Cite
|
Sign up to set email alerts
|

Pod and Seed Trait QTL Identification To Assist Breeding for Peanut Market Preferences

Abstract: Although seed and pod traits are important for peanut breeding, little is known about the inheritance of these traits. A recombinant inbred line (RIL) population of 156 lines from a cross of Tifrunner x NC 3033 was genotyped with the Axiom_Arachis1 SNP array and SSRs to generate a genetic map composed of 1524 markers in 29 linkage groups (LG). The genetic positions of markers were compared with their physical positions on the peanut genome to confirm the validity of the linkage map and explore the dist… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 88 publications
2
21
0
Order By: Relevance
“…Luo et al [20] also identified a similar region on chromosome A07 (from 0.06 to 1.54 Mb), as containing major, stable and co-localized QTLs involved in pod weight and size variation that explained up to 43.62% of phenotypic variation. This region colocalized with the pod and seed size QTL cluster reported by Chavarro et al [26] around 0.63-1.03 Mb. Finally, Zhuang et al [7] reported the same region on chromosome A07 (0.87 to 1.9 Mb) as containing a QTL that controlled pod and seed size.…”
Section: Candidate Genes Associated With Seed Size Are Found In the Qsupporting
confidence: 66%
See 1 more Smart Citation
“…Luo et al [20] also identified a similar region on chromosome A07 (from 0.06 to 1.54 Mb), as containing major, stable and co-localized QTLs involved in pod weight and size variation that explained up to 43.62% of phenotypic variation. This region colocalized with the pod and seed size QTL cluster reported by Chavarro et al [26] around 0.63-1.03 Mb. Finally, Zhuang et al [7] reported the same region on chromosome A07 (0.87 to 1.9 Mb) as containing a QTL that controlled pod and seed size.…”
Section: Candidate Genes Associated With Seed Size Are Found In the Qsupporting
confidence: 66%
“…Several studies reported QTLs controlling pod/seed weight and size in peanut [12,[15][16][17][18][19][20][21][22][23][24][25][26]. However, a few of them involved crosses between wild and cultivated species.…”
Section: Introductionmentioning
confidence: 99%
“…With the advancement of SNP array technology [ 19 , 20 ], the limitation of genetic map density was alleviated by a drastic increase in genetic markers for map construction. Close to 1000 SNP markers were placed on peanut linkage maps recently [ 21 , 22 ]. In addition to the low polymorphism, another challenge is to perform phenotyping on TTM due to the unique underground formation of fruit, the indeterminate nature of pod formation, and the application of the commonly used but laborious and somewhat subjective hull-scrape method to determine pod maturity [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The genetic map employed in this study consisted of 4561 bin markers and spanned a length of 2032.39 cM with an average genetic distance of 0.45 cM. Both marker number and marker density were larger than those reported for other recent peanut linkage maps [1,[14][15][19][20]. This nding might be attributable to the large size of the population used in this study and/or the whole genome resequencing strategy adopted, which is more appropriate for tetraploids with respect to other sequencing technologies.…”
Section: Annotation Of Genes and Validation Of The Snps In The Qtl Inmentioning
confidence: 94%
“…With advances in next-generation sequencing (NGS) technology and the availability of reference genomes for diploid progenitors and cultivated peanut [9][10][11][12], high-resolution mapping has been successfully performed for complex traits in peanut, such as yield [13,14] and disease resistance [15][16][17]. In peanut, various NGS methods have been employed to generate a large number of SNPs, such as restriction-site-associated DNA sequencing (RAD-seq) [17][18], single nucleotide polymorphism (SNP) array [19][20], speci c-locus ampli ed fragment sequencing (SLAF-seq) [13,21], diversity array technology (DArT) [4,22], and whole genome resequencing (WGRS) [15].…”
Section: Introductionmentioning
confidence: 99%